Methimazole induces dose-dependent cardiotoxicity via disrupting Hippo/YAP and calcium handling pathway: An echocardiographic, molecular, and histological investigation - Aqsa Bibi; Salim Jamil; Mansour Abdulaziz Alsaleem; Hesham M. Hassan; Khalaf F. Alsharif; Fuad M. Alzahrani; Khalid J. Alzahrani; Muhammad Tahir Naseem (Tissue and Cell, 2027)

Dose-dependent neurotoxic effects of anastrozole via disrupting NLRP3 inflammasome and α-synuclein pathways - Amani Alghamdi; Salim Jamil; Abdulaziz Saleh Alkhoshaiban; Muhammad Bilal Azmat; Fuad M. Alzahrani; Khalid J. Alzahrani; Khalaf F. Alsharif; Hesham M. Hassan (Tissue and Cell, 2026)

Sensors and smart food packaging for supply chains: Bridging expiration dates and actual perishability - Muhammad Umar Azam; Jolina Rodrigues; Mohamed Hamid Salim; Sarath Haridas Kaniyamparambil; Khalid Askar; Imane Belyamani; Blaise L. Tardy; Nouha Alcheikh (Food Control, 2026)

Chronic labetalol exposure induced dose-dependent testicular toxicity via disrupting HPG-axis, spermatogenesis and steroidogenic pathways: A biochemical, molecular and histopathological evidence - Salim Jamil; Fuad M. Alzahrani; Khalaf F. Alsharif; Khalid J. Alzahrani; Muhammad Bilal Azmat; Hesham M. Hassan; Muhammad Tahir Naseem (Tissue and Cell, 2026)

Enhancing whale shark (Rhincodon typus) conservation through Marxan-based spatial analysis in Saleh Bay - Amanda D. Putri; Yulius; Syamsul Bahri Agus; Taslim Arifin; Ulung Jantama Wisha; Rinny Rahmania; Hadiwijaya L. Salim; Joko Prihantono; Aida Heriati; Aprizon Putra; Arya Ningsih; Fery Kurniawan; et al. (Environmental Development, 2026)

Breeding practices and production systems of indigenous goats in two agro-ecological zones of North Maluku Province, Indonesia - Dwi Nur Happy Hariyono; Muhammad Ade Salim; Dyah Maharani; Eny Endrawati (Tropical Animal Health and Production, 2026)

Structure Guided Identification of Small Molecule Inhibitors Targeting Staphylococcus aureus α-Hemolysin - Saeed Ullah Khattak; Nida Raza; Mawahib Ahmed; Ayesha Saleem; Muhammad Salim; Sajjad Ahmad (Journal of Pharmaceutical Innovation, 2026)

Protective effects of linagliptin and tenofovir disoproxil fumarate against APAP-induced acute liver injury: A biochemical, histological, and computational study - Mahnoor Yamin; Muhammad Ali; Arifa Mehreen; Bushra Akhtar; Mansour Abdulaziz Alsaleem; Salim Jamil; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

Tapentadol induces progressive hepatic damage via disrupting Hippo–YAP and bile acid–FXR pathways: An integrated experimental and computational perspective - Han Hu; Salim Jamil; Muhammad Bilal Azmat; Mohammed Alissa; Ghfren S. Aloraini; Amal A. Albati; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

Corrigendum to “A Source-Environment-Response (SER) approach for solving Spatio-temporal radon transport in different media” [J. Atmos. Sol. Terr. Phys.- 282, May (2026), 106796] - Ahmad Muhammad; Ibrahim Yahaya Muhammad; Ahmed H. Ali; Muhammad Abubakar Isah; Salim Jibrin Danbatta; Ahmed Sait Alali (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Gillnet Catch Composition and Selectivity for Giant Sea Catfish Netuma thalassina in a Tropical Estuarine Fishery of Tarakan Waters, Indonesia - Gazali Salim; Mujiyanto Mujiyanto; Christine Dyta Nugraeni; Muhammad Gandri Haryono; Hairudin Hairudin; Masnia Masnia; Fani Lestari; Agus Indarjo; Sitti Hartinah; Yayuk Sugianti (Thalassas: An International Journal of Marine Sciences, 2026)

Attenuating the Dual Injury of Deficit Irrigation and Salinity On Wheat Physiology and Productivity Via Amending Soil with Compost and Biochar - Ahmed R. Abd El-Tawwab; Khaled M. A. Ramadan; Basma R. Abdel-Moatamed; Shimaa A. Abd El-Mageed; Sallah A. Al Hashedi; Zafar Iqbal; Salim A. Ali; Muhammad Munir; Hani S. Saudy; Taia A. Abd El-Mageed (Journal of Crop Health, 2026)

Evaluation and progression of marine heatwaves over the northwestern Indian Ocean: A comparative study using satellite and numerical model data - Akurathi Venkata Sai Chaitanya; Abdul Azeez Saleem; Muhammad Shafeeque; Salim Lateef; Mohamed Asharaf; Jiya Albert (Regional Studies in Marine Science, 2026)

A Source-Environment-Response (SER) approach for solving Spatio-Temporal Radon Transport in Different Media - Ahmad Muhammad; Ibrahim Yahaya Muhammad; Ahmet H. Ali; Muhammad Abubakar Isah; Salim Jibrin Danbatta; Ahmet Ali Sait (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Plant growth promoting bacteria regulate antioxidant synthesis in wheat under chromium stress leading to stabilization in photosynthetic activity - Modhi O. Alotaibi; Sibgha Noreen; Muhammad Salim Akhter; Tariq Mahmood Khan; Suliman Mohammed Suliman Alghanem; Faizah Amer Altihani; Qafia Naz Aslam; Mohamed Hashem; Omar Mahmoud Al-zoubi (Physiology and Molecular Biology of Plants, 2026)

Synthesis of biocompatible novel multi-tailed indole-based resorcinarene for effective delivery of quercetin against multidrug-resistant S. aureus - Khadija Rehman; Tasmina Kanwal; Muhammad Hasnain; Rukesh Maharjan; Wajeeha Muzafar; Komal Rao; Salim Saifullah; Shabana Usman Simjee; Muhammad Raza Shah (Archives of Microbiology, 2026)

Homopterocarpin alleviates methoxychlor-induced hepatotoxicity via modulating thioredoxin/peroxiredoxin and TLR4/MyD88 pathway: A comprehensive biochemical, histopathological, and computational analysis - Mansour Abdulaziz Alsaleem; Salim Jamil; Abdulaziz Saleh Alkhoshaiban; Muhammad Bilal Azmat; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

Unveiling Hidden Threats: Molecular Detection and Genetic Diversity of Hepatozoon spp. and Toxoplasma Gondii in Wild Rodents of Saudi Arabia and Their Ectoparasites - Maryam Ijaz; Samia Q. Alghamdi; Abdullah D Alanazi; Mubashra Salim; Muhammad Naeem; Muhammad Ali; Shabana Mukhtiar; Kasim Sakran Abass; Hira Muqaddas; Adil Khan; Furhan Iqbal (Acta Parasitologica, 2026)

Spherical fuzzy evidential reasoning for vehicle-to-grid enabled electric vehicle adoption: A data-driven analysis of public perception - Muhammad Zahid; Ezzeddin Bakhtavar; Salim Khoso; Syed Naveel Hussain; Rehan Sadiq; Kasun Hewage (Travel Behaviour and Society, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Structural, dielectric, and microstructural properties of Bi0.5(Na0.82K0.18)0.5Ti1–xNbxO3 ceramics: Effect of Nb doping on phase transition, grain growth, and electrical performance for dielectric, piezoelectric and energy storage applications - Salim Ullah; Zahid Ullah; Muhammad Amir Khan; Amir Ullah (Next Research, 2026)

Sulfoxaflor provokes progressive myocardial injury by disrupting HIF-1α/VEGFA signaling, redox balance, and inflammation: A comprehensive biochemical, echocardiographic, and histopathological approach - Yingying Dong; Salim Jamil; Mahmoud El Safadi; Ali Akbar; Muhammad Faisal Hayat; Ahmed Al-Emam; Hesham M. Hassan (Journal of Environmental Sciences, 2026)

Global manta and devil ray population declines: Closing policy and management gaps to reduce fisheries mortality - Betty J.L. Laglbauer; Nidhi G. D'Costa; Joshua D. Stewart; Marta D. Palacios; Melissa Cronin; Daniel Fernando; Nerea Lezama-Ochoa; Asia O. Armstrong; Rima W. Jabado; Sarah Fowler; Julia M. Lawson; Olga Koubrak; et al. (Biological Conservation, 2026)

Sediment transport modeling of trenching activities: a case study for the Safaniya coastal waters in the Arabian Gulf - Abdul Azeez Saleem; Akurathi V. S. Chaitanya; Salim Lateef; Jiya Albert; Muhammad Shafeeque; Karuppasamy P. Manikandan; Thadickal V. Joydas; Mohamed Asharaf; Luai M Alhems; Ali M. Qasem; Sabique Langodan; Diego Lozano-Cortés (Ocean Dynamics, 2026)

Molybdenum induces hepatic impairments via dysregulating NLRP3, JAK1/STAT3 and NF-κB pathways: A dose dependent toxicity assessment - Mahmoud El Safadi; Abdulaziz Saleh Alkhoshaiban; Muhammad Faisal Hayat; Syeda Sania Zahara; Ali Akbar; Maha A. Al-Aream; Salim Jamil; Hesham M. Hassan (Journal of Trace Elements in Medicine and Biology, 2025)

Optimizing hybrid insulation systems for diverse climates: A comparative analysis of composite material combinations in residential buildings - Salim Khoso; Ezzeddin Bakhtavar; Ahmed Abouyoussef; Muhammad Zahid; Kasun Hewage; Rehan Sadiq (Energy and Buildings, 2025)

Sofosbuvir containing ph-responsive hydrogel microparticulate system: design, characterization, and biocompatibility assessment - Muhammad Aun; Muhammad Umar Ashraf; Salim Albukhaty; Umaira Rehman; Asif Mahmood; Asma Razzaq; Hira Ijaz; Rai Muhammad Sarfraz; Mohamed M. Salem; Areej Alsubaie; Mounir M. Bekhit (Journal of Pharmaceutical Innovation, 2025)

Chlorophyll-a modulation in the Arabian Gulf using two decades of merged ocean-color data - Muhammad Shafeeque; Abdul Azeez Saleem; Akurathi V. S. Chaitanya; C. P. Abdulla; Salim Lateef; Jiya Albert (Frontiers in Marine Science, 2025)
Introduction The Arabian Gulf (Gulf) is a dynamic marine ecosystem in which phytoplankton productivity, indicated by Chlorophyll- a (Chl- a ), is strongly affected by environmental and climatic variables. Understanding the spatiotemporal variability of Chl- a and its driving environmental factors is critical for assessing primary productivity and ecosystem dynamics of the Gulf. Methods This study investigated the long-term Chl- a variability and its dynamic response to environmental variables in the Gulf using two decades (2003 to 2023) of Chl- a data from merged multi-sensor Ocean Colour Climate Change Initiative. We adopted an integrated approach that includes climatology, multivariate statistical analysis, interannual variability and trend analysis to evaluate Chl- a variability and identify its dominant drivers. Results Seasonal climatology exhibited a marked winter bloom driven by convective mixing and nutrient replenishment, followed by a summer decline due to strong stratification. Box average analysis using correlogram and principal component analysis for selected regions revealed distinct regional patterns, with the northern and central Gulf showing higher variability. The results further highlighted sea surface temperature (SST), sea surface salinity, photosynthetically available radiation and wind speed as primary drivers of Chl- a variability in the Gulf. The interannual variability of Chl- a peaks along the central eastern Gulf in winter and central western Gulf during summer, highlighting regional heterogeneity in phytoplankton dynamics. Long-term spatial trend analysis of Chl- a , net primary productivity (NPP) and SST indicated overall decreasing trend in Chl- a and NPP, particularly along the north and eastern coasts of the Gulf; and warming SST in the northern and central Gulf. Discussion The results indicate the requirement of further research on the complex interplay between physical and biogeochemical factors, and anthropogenic influences on Chl- a distribution, which can help future monitoring and predictive ecosystem models for the Gulf under changing climate conditions.

Development and characterization of Zingiber zerumbet rhizome crude extract-loaded nanoemulsions: In vitro release and cytotoxicity assessment against MDA-MB-231 breast cancer cell line - Zahra Sanaimehr; Norazlinaliza Salim; Emilia Abdulmalek; Intan Nur Fatiha Shafie; Muhammad Alif Mohammad Latif; Renny Apriliana M. Ansori; Sharida Fakurazi (South African Journal of Botany, 2025)

LYCOPENE β-CYCLASE overexpression improves growth, modulates hormone content, and affects rhizospheric interactions in tobacco and tomato roots - Alice Stra; Juan C. Moreno; Jian You Wang; Ivan Petrik; Cristina Votta; Muhammad Jamil; Kit Xi Liew; Guan-Ting Erica Chen; Yagiz Alagoz; Claudia Stange; Valentina Fiorilli; Ondrej Novak; et al. (Plant Cell Reports, 2025)

High take of mobulid rays in East Java, Indonesia: landing trends and socio-economic context - Betty J. L. Laglbauer; Muhammad G. Salim; Fahmi; Selvia Oktaviyani; Irianies C. Gozali; Firmansyah Tawang; Hasan S. Rizal; Vidlia P. Rosady; Didik Rudianto; Isabel Ender; Jorge M. R. Fontes; Pedro Afonso; et al. (Environmental Biology of Fishes, 2025)

Predicting water quality variables using gradient boosting machine: global versus local explainability using SHapley Additive Explanations (SHAP) - Khaled Merabet; Fabio Di Nunno; Francesco Granata; Sungwon Kim; Rana Muhammad Adnan; Salim Heddam; Ozgur Kisi; Mohammad Zounemat-Kermani (Earth Science Informatics, 2025)

Correction: Mimics of the Growth Regulator Zaxinone Increase Saffron Yield and Improve its Nutritional Value - Arshad Jalal; Mohamed E. Abdelaziz; Mohamed Salem; Kit Xi Liew; Jian You Wang; Wafa Alrasheed; Talal K. Al-Ateeq; Sahar Althobiti; Muien Qaryouti; Abdulrahman Al-Soqeer; Muhammad Jamil; Salim Al-Babili (Journal of Plant Growth Regulation, 2025)

Mimics of the Growth Regulator Zaxinone Increase Saffron Yield and Improve its Nutritional Value - Arshad Jalal; Mohamed E. Abdelaziz; Mohamed Salem; Kit Xi Liew; Jian You Wang; Wafa Alrasheed; Talal K. Al Ateeq; Sahar Althobiti; Muien Qaryouti; Abdulrahman Al Soqeer; Muhammad Jamil; Salim Al‐Babili (Journal of Plant Growth Regulation, 2025)

Enhancing Drought Tolerance in Bread Wheat Through GABA Seed Priming and Optimized Storage Temperatures - Salim Humaid Al Ghafri; Waleed M. Al-Busaidi; Muhammad Farooq (Journal of Plant Growth Regulation, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Highly sensitive electrochemical sensing of fipronil using a ZnO/Graphene@C-dots hybrid nanocomposite - La Ode Agus Salim; Paulina Taba; Muhammad Zakir; Muhammad Nurdin; Abdul Wahid Wahab; Dahlang Tahir; St. Fauziah; Akrajas Ali Umar (Environmental Nanotechnology, Monitoring & Management, 2025)

Advanced TiO2-ZnO/graphene hybrid nanocomposite for ultra-sensitive electrochemical detection of fipronil pesticide - La Ode Agus Salim; Muhammad Nurdin; Maulidiyah Maulidiyah; Nohong Nohong (Environmental Nanotechnology, Monitoring & Management, 2025)

Forecasting maximal and minimal air temperatures using explainable machine learning: Shapley additive explanation versus local interpretable model-agnostic explanations - Noureddine Daif; Fabio Di Nunno; Francesco Granata; Salah Difi; Ozgur Kisi; Salim Heddam; Sungwon Kim; Rana Muhammad Adnan; Mohammad Zounemat-Kermani (Stochastic Environmental Research and Risk Assessment, 2025)

Enhancing BOD5 forecasting accuracy with the ANN-Enhanced Runge Kutta model - Rana Muhammad Adnan; Ahmed A. Ewees; Mo Wang; Ozgur Kisi; Salim Heddam; Kulwinder Singh Parmar; Mohammad Zounemat-Kermani (Journal of Environmental Chemical Engineering, 2025)

In-Situ Self-Transformation Growth of Binary g-C3N4/CdS Heterojunctions for Efficient Hydrogen Evolution and Wastewater Treatment - Muhammad Irfan; Muhammad Shoaib; Humaira Hussain; Muhammad Yasin Naz; Shazia Shukrullah; Saifur Rahman; Salim Nasar Faraj Mursal; Abdulnour Ali Jazem Ghanim (Water, Air, & Soil Pollution, 2025)

Heavy Metal Concentrations in Water, Sediment, and Fish Species in Chashma Barrage, Indus River: A Comprehensive Health Risk Assessment - Khalid Hussain Rind; Sonia Aslam; Nazakat Hussain Memon; Asif Raza; Muhammad Qamar Saeed; Alia Mushtaq; Javed Ahmed Ujan; Syed Fahad Habib; Salim S. Al-Rejaie; Mohamed Mohany (Biological Trace Element Research, 2025)

Implications of Heavy Metal Accumulation in Fish Feed, Water, Sediment, and Different Fish Species in a Polyculture System - Allah Bachayo Rajar; Zainab Malik; Javed Ahmed Ujan; Khalid Hussian Rind; Raqeeb Ullah; Saira Naz; Mujeeb Ullah; Muhammad Zahid; Khalid Khan; Khayyam Khayyam; Salim S. Al-Rejaie; Mohamed Mohany (Biological Trace Element Research, 2025)

Environmental assessment of cenosphere and GGBFS-based geopolymers: A path to greener construction materials - Muhammad Usama Salim; Aamar Danish; Anthony S. Torres; Carlos Moro (Environmental Impact Assessment Review, 2025)

Sublethal Concentrations of Cadmium and Lead: Effects on Hemato-Biochemical Parameters and Tissue Accumulation in Wallagu attu - Rim EL Amouri; Javed Ahmed Ujan; Asif Raza; Alia Mushtaq; Muhammad Qamar Saeed; Samrah Masud; Syed Sikandar Habib; Marija Milošević; Salim S. Al-Rejaie; Mohamed Mohany (Biological Trace Element Research, 2025)

Electronic, thermoelectric and magnetic properties of ternary telluride KAlTe2 and KInTe2 from theoretical perspective - Zahid Ullah; Muhammad Amir; Aiman Bazilla; Salim Ullah; Umar Shahzad; Nazir Ullah; Jabir Khan; Sabahat Gul (Next Research, 2024)

Combined environmental relevant exposure to perfluorooctanoic acid and zinc sulfate enhances apoptosis through binding with endogenous antioxidants in Daphnia magna - Naima Hamid; Muhammad Junaid; Nurhayati Binti Salim; Rakia Manzoor; Ong Meng Chuan (Food and Chemical Toxicology, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Ascorbic acid-mediated enhancement of antioxidants and photosynthetic efficiency: A strategy for enhancing canola yield under salt stress - Nawishta Saleem; Sibgha Noreen; Muhammad Salim Akhter; Mohammed O. Alshaharni; Habib-ur-Rehman Athar; Fahad Mohammed Alzuaibr; Omar Mahmoud Al-zoubi; Seema Mahmood (South African Journal of Botany, 2024)

Heterologous expression of distinct insecticidal genes in potato cultivars encodes resistance against potato tuber moth, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) - Muhammad Salim; Allah Bakhsh; Muhammad Nadir Naqqash; Ayhan Gökçe (Journal of Plant Diseases and Protection, 2024)
The potato tuber moth, Phthorimaea operculella (Zeller), is a notorious insect pest of potato incurring substantial yield losses in the field as well as in storage. Chemical control is difficult to exercise due to the latent feeding of the caterpillars and their ability to develop resistance against insecticides. One of the essential components of efficient insect-resistant management is using two or more different insecticidal genes in transgenic crops to effectively avoid and delay the resistance development in insect pests. Two constructs, namely DS-1 ( cry3A + SN-19 genes) and DS-2 ( OCII + SN-19 genes) in pCAMBIA1301 binary vector, were developed and were transformed in potato cultivars (Agria and Lady Olympia) via Agrobacterium -mediated transformation. The molecular analysis confirmed gene integration and expression of the introduced genes in transgenic plants. The insecticidal effects of incorporated genes in transgenic plants were assessed against 1st, 2nd, 3rd, and 4th instar potato tuber moth (PTM) larvae. The transgenic plants endured significantly high mortalities (100%) of larval stages of PTM within 72 h. Our results show that these transgenic potato plants have the potential to control populations of PTM and are also useful tools in managing PTM that would ultimately reduce the dependency on conventional chemical pesticides with potentially less or minimal hazards. These lines can also serve as an excellent source of germplasm for potato breeding program.

In-depth analysis of ambient air pollution changes due to the COVID-19 pandemic in the Asian Monsoon region - Mohd Talib Latif; Noorain Purhanudin; Nur Zulaikha Mohd Afandi; Maria Obiminda L. Cambaliza; Nor Diana Abdul Halim; Nor Syamimi Sufiera Limi Hawari; To Thi Hien; Ohnmar May Tin Hlaing; Warnakulasuriya Roshani Loreta Hiranthi Jansz; Muhammad Fahim Khokhar; Puji Lestari; Shih-Chun Candice Lung; et al. (Science of The Total Environment, 2024)

Assessment of heavy metal levels in polyculture fish farms and their aquatic ecosystems: an integrative study addressing environmental and human health risks associated with dam water usage - Syed Sikandar Habib; Saira Naz; Muhammad Qamar Saeed; Javed Ahmed Ujan; Samrah Masud; Alia Mushtaq; Mujeeb Ullah; Khalid Khan; Muhammad Zahid; Salim S. Al-Rejaie; Mohamed Mohany (Environmental Geochemistry and Health, 2024)

Hope or hype? Evaluating the environmental footprint of reclaimed fly ash in geopolymer production - Aamar Danish; Anthony S. Torres; Carlos Moro; Muhammad Usama Salim (Resources, Conservation and Recycling, 2024)

Income inequality of tribal households in Bangladesh: A decomposition analysis - Romaza Khanum; Nosrat Jahan; Muhammad Salim Al Mahadi (Environmental Development, 2024)

Analyzing the impact of pesticides on the indus river: contamination levels in water, sediment, fish, and associated human health risks - Syed Sikandar Habib; Francesco Fazio; Samrah Masud; Javed Ahmed Ujan; Muhammad Qamar Saeed; Mujeeb Ullah; Khalid Khan; Khayyam Khayyam; Mohamed Mohany; Marija Milošević; Salim S. Al-Rejaie; Cristina Cravana (Environmental Geochemistry and Health, 2024)

A comprehensive review of navigating urbanization induced climate change complexities for sustainable groundwater resources management in the Indian subcontinent - Md Zakaria Salim; Namit Choudhari; Abdulla - Al Kafy; Hrithik Nath; Saleh Alsulamy; Zullyadini A. Rahaman; Adel S. Aldosary; Muhammad Tauhidur Rahmand; Baqer Al-Ramadan (Groundwater for Sustainable Development, 2024)

Integrated facies analysis of the Late Cretaceous Simsima Formation in northwestern Oman mountain, Jabel Al-Rawdah, Hatta area, Oman - Mithaa Salim Al-Jabri; Iftikhar Ahmed Abbasi; Muhammad Hanif; Mohamed A. K. El-Ghali; Abdulrazaq Al Sayigh (Arabian Journal of Geosciences, 2024)

Health, environment, and sustainable development: evidence from panel data from ASEAN countries - Muhammad Azam; Faridul Islam; Salim Rashid (Air Quality, Atmosphere & Health, 2024)

Unlocking Triticum aestivum L. resilience: Exogenous proline's remarkable role in mitigating lead stress, and delving into the secrets of TaGSK1 gene expression - Sidra Balooch; Sibgha Noreen; Seema Mahmood; Nida Zahra; Ahmad Azeem; Muhammad Mohsin Altaf; Muhammad Salim Akhter; Adeel Abbas (South African Journal of Botany, 2024)

Enhancing systematic tolerance in Bermuda grass (Cynodon dactylon L.) through amplified alkB gene expression and bacterial-driven hydrocarbon degradation - Sehrish Iqbal; Ume Ummara; Sibgha Noreen; Muhammad Salim Akhter; Farrukh Jaleel; Shazia Jabeen; Nargis Naz; Abdul Wahid; Modhi O. Alotaibi; Mudawi M. Nour; Rahmah N. Al-Qthanin; Muhammad Aqeel (Environmental Science and Pollution Research, 2024)

Forecasting monthly rainfall using hybrid time-series models and Monte Carlo simulation amidst security challenges: a case study of five districts from northern Nigeria - Salim Jibrin Danbatta; Ahmad Muhammad; Asaf Varol; Daha Tijjani Abdurrahaman (Environment, Development and Sustainability, 2024)
Nigeria’s agricultural sector relies heavily on rainfall, but insecurity in various regions poses significant challenges. This study aims to address this issue by identifying secure, rain-rich areas in northern Nigeria to support sustainable agriculture. Two models, one integrating classical statistical methods (polynomial and Fourier series fittings) and another using a hybrid approach (artificial neural networks, polynomial, and Fourier series fittings), were employed to analyze historical rainfall data from 1981 to 2021 in the selected districts (Kano, Zaria, Bida, Nguru, and Yelwa) known for their rainfall levels and security stability. The study demonstrates that the machine learning-classical hybrid model outperforms existing models, including the classical-classical hybrid and benchmark models like Iwok’s (2016) model, Fourier series, and SARIMA models. Multi-step ahead forecasting with this hybrid model reveals potential changes in rainfall patterns. Notably, Kano, Zaria, Bida, and Yelwa are expected to experience increased rainfall from 2022 to 2026, while Nguru may initially witness decreased rainfall, with improvement in the final year (2026). In conclusion, this study introduces an effective approach for rainfall modeling and forecasting, facilitating the identification of secure agricultural regions in northern Nigeria. These findings carry implications for crop production and agricultural development, contributing to climate resilience efforts and assisting stakeholders in strategic decision-making for regional agricultural investments.

Improved prediction of monthly streamflow in a mountainous region by Metaheuristic-Enhanced deep learning and machine learning models using hydroclimatic data - Rana Muhammad Adnan; Amin Mirboluki; Mojtaba Mehraein; Anurag Malik; Salim Heddam; Ozgur Kisi (Theoretical and Applied Climatology, 2024)

Population structure of endangered spinetail devil ray (Mobula mobular) in the Lesser Sunda Seascape, Indonesia, revealed using microsatellite and mitochondrial DNA - Muhammad Danie Al Malik; Mochamad Iqbal Herwata Putra; Edy Topan; Ni Luh Astria Yusmalinda; Ni Putu Dian Pertiwi; Yuliana Fitri Syamsuni; Ni Kadek Dita Cahyani; Enex Yuni Artiningsih; Sarah Lewis; Lumban Nauli Lumban Toruan; Muhammad Ghozaly Salim; Firmansyah Tawang; et al. (Aquatic Sciences, 2024)

An integrated satellite characterization and hydrodynamic study in assessing coastal dynamics in Cirebon, West Java - Karlina Triana; Tubagus Solihuddin; Semeidi Husrin; Johan Risandi; Eva Mustikasari; Terry Louise Kepel; Hadiwijaya Lesmana Salim; Nasir Sudirman; Akhmad Tri Prasetyo; Muhammad Helmi (Regional Studies in Marine Science, 2023)

Exploring soil radon (Rn) concentrations and their connection to geological and meteorological factors - Ahmad Muhammad; Salim Jibrin Danbatta; Ibrahim Yahaya Muhammad; Ibrahim Isah Nasidi (Environmental Science and Pollution Research, 2023)

Urbanization, rural energy-poverty, and carbon emission: unveiling the pollution halo effect in 48 BRI countries - Qi Xu; Salim Khan; Xiaojuan Zhang; Muhammad Usman (Environmental Science and Pollution Research, 2023)

Modelling biochemical oxygen demand using improved neuro-fuzzy approach by marine predators algorithm - Rana Muhammad Adnan; Hong-Liang Dai; Ozgur Kisi; Salim Heddam; Sungwon Kim; Christoph Kulls; Mohammad Zounemat-Kermani (Environmental Science and Pollution Research, 2023)
Biochemical oxygen demand (BOD) is one of the most important parameters used for water quality assessment. Alternative methods are essential for accurately prediction of this parameter because the traditional method in predicting the BOD is time-consuming and it is inaccurate due to inconstancies in microbial multiplicity. In this study, the applicability of four hybrid neuro-fuzzy (ANFIS) methods, ANFIS with genetic algorithm (GA), ANFIS with particle swarm optimization (PSO), ANFIS with sine cosine algorithm (SCA), and ANFIS with marine predators algorithm (MPA), was investigated in predicting BOD using distinct input combinations such as potential of hydrogen (pH), dissolved oxygen (DO), electrical conductivity (EC), water temperature (WT), suspended solids (SS), chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (T-P) acquired from two river stations, Gongreung and Gyeongan, South Korea. The applicability of multi-variate adaptive regression spline (MARS) in determination of the best input combination was examined. The ANFIS-MPA was found to be the best model with the lowest root mean square error and mean absolute error and the highest determination coefficient. It improved the root mean square error of ANFIS-PSO, ANFIS-GA, and ANFIS-SCA models by 13.8%, 12.1%, and 6.3% for Gongreung Station and by 33%, 25%, and 6.3% for Gyeongan Station in the test stage, respectively.

Disruption of the cytochrome CYP711A5 gene reveals MAX1 redundancy in rice strigolactone biosynthesis - Jian You Wang; Guan-Ting Erica Chen; Justine Braguy; Muhammad Jamil; Lamis Berqdar; Salim Al-Babili (Journal of Plant Physiology, 2023)

Enhancing accuracy of extreme learning machine in predicting river flow using improved reptile search algorithm - Rana Muhammad Adnan; Reham R. Mostafa; Hong-Liang Dai; Salim Heddam; Adil Masood; Ozgur Kisi (Stochastic Environmental Research and Risk Assessment, 2023)

Unlocking sustainable supply chain performance through dynamic data analytics: a multiple mediation model of sustainable innovation and supply chain resilience - Arsalan Zahid Piprani; Syed Abdul Rehman Khan; Rabiya Salim; Muhammad Khalilur Rahman (Environmental Science and Pollution Research, 2023)

Demographic features and population projection of resistant and susceptible populations of Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) - Muhammad Nadir Naqqash; Ayhan Gökçe; Allah Bakhsh; Muhammad Salim (Phytoparasitica, 2023)

Silicon Supplement Improves Growth and Yield Under Salt Stress by Modulating Ionic Homeostasis and Some Physiological Indices in Hordeum vulgare L - Muhammad Salim Akhter; Sibgha Noreen; Seema Mahmood; Muhammad Aqeel; Zafar Ullah Zafar; Muhammad Rashid; Muhammad Naveed Arshad; Muhammad Owais; Javid Ahmad; Kausar Hussain Shah (Journal of Soil Science and Plant Nutrition, 2023)

Global declarations on electric vehicles, carbon life cycle and Nash equilibrium - Baher Bakhtyar; Zhang Qi; Muhammad Azam; Salim Rashid (Clean Technologies and Environmental Policy, 2023)
Universal environmental policies adopt strategies that enhance and encourage the production and usage of electric vehicles (EVs). Universal cooperation is evident in the framework of agreements or protocols so as to successfully lead countries towards the predetermined goals. The question is whether this trend can reduce global warming or CO 2 emissions worldwide. By adopting game theory, this study analyses electricity carbon life cycle in leading EV countries. Results show that although the spread of EVs in Europe and the USA can mitigate carbon emissions, the production and use of electric vehicles in some countries, such as China and India, become a new source of such emissions. This reverse effect is due to the emission of greenhouse gases from electricity sources in these countries. Game theory also suggests that countries with unclean electricity sources should reconsider their plans to produce and use EVs. This study confirms that although carbon emission and global warming are global problems, regional and local policies can be substituted with a single comprehensive approach for an effective means of CO 2 emission reduction. Graphical abstract

From knowledge to action: multi-stakeholder planning for urban climate change adaptation and resilience in the Asia–Pacific - Micah R. Fisher; Keith A. Bettinger; Kem Lowry; Muhammad Ridwan Lessy; Wilmar Salim; Dolores Foley (Socio-Ecological Practice Research, 2022)

Sedimentology and diagenesis control on reservoir quality of Sheikhan Limestone (Eocene) at the Panoba and Sheikhan Nala Section, Kohat Basin, Pakistan - Atif Salim; Muhammad Kashif; Bin Dou; Danish Khan; Muhammad Jawad Munawar; Noor Ahmed; Naveed Rehman; Muhammad Sajid; Zahid Ullah; Muhammad Tariq (Carbonates and Evaporites, 2022)

9-cis-β-Apo-10ʹ-carotenal is the precursor of strigolactones in planta - Guan-Ting Erica Chen; Jian You Wang; Muhammad Jamil; Justine Braguy; Salim Al-Babili (Planta, 2022)

The mechanism of alkali-aggregate reaction in concrete/mortar and its mitigation by using geopolymer materials and mineral admixtures: a comprehensive review - Muhammad Usama Salim; Mohammad Ali Mosaberpanah (European Journal of Environmental and Civil Engineering, 2022)

Crisis Ocean Modelling with a Relocatable Operational Forecasting System and Its Application to the Lakshadweep Sea (Indian Ocean) - Georgy I. Shapiro; Jose M. Gonzalez-Ondina; Mohammed Salim; Jiada Tu; Muhammad Asif (Journal of Marine Science and Engineering, 2022)
This study presents the Relocatable Operational Ocean Model (ReOMo), which can be used as a Crisis Ocean Modelling System in any region of the global ocean that is free from ice. ReOMo can be quickly nested into an existing coarser resolution (parent) model. The core components of ReOMo are the NEMO hydrodynamic model and Rose-Cylc workflow management software. The principal innovative feature of ReOMo is the use of the Nesting with Data Assimilation (NDA) algorithm, which is based on the model-to-model assimilation technique. The NDA utilises the full 3D set of field variables from the parent model rather than just the 2D boundary conditions. Therefore, ReOMo becomes physically aware of observations that have been assimilated and dynamically balanced in the external model. The NDA also reduces the spatial phase shift of ocean features known as the ‘double penalty effect’. In this study, ReOMo was implemented for the Lakshadweep Sea in the Indian Ocean at 1/20°, 1/60°, or 1/120° resolution with and without model-to-model data assimilation. ReOMo is computationally efficient, and it was validated against a number of observational data sets to show good skills with an additional benefit of having better resolution than the parent model.

Mass Transfer Kinetics and Mechanisms of Phosphate Adsorbed on Waste Mussel Shell - Nur Atikah Abdul Salim; Mohamad Ali Fulazzaky; Mohd Hafiz Puteh; Mohd Hairul Khamidun; Abdull Rahim Mohd Yusoff; Noorul Hudai Abdullah; Mohammad Fulazzaky; Muhammad Abbas Ahmad Zaini (Water, Air, & Soil Pollution, 2022)

Reliability of the Mass Transfer Factor Models to Describe the Adsorption of NH4+ by Granular Activated Carbon - Mohamad Ali Fulazzaky; Nur Atikah Abdul Salim; Mohd Hafiz Puteh; Mohd Hairul Khamidun; Abdull Rahim Mohd Yusoff; Mohammad Fulazzaky; Noorul Hudai Abdullah; Muhammad Abbas Ahmad Zaini (International Journal of Environmental Research, 2022)

Demographic study of imidacloprid-resistant Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) fed on transgenic and commercial potato cultivars - Muhammad Salim; Ayhan Gökçe; Allah Bakhsh (Phytoparasitica, 2022)

An analysis on the effect of coronavirus (COVID-19) pandemic movement control order (MCOS) on the solid waste generation in Peninsular Malaysia - Muhammad Afiq Brohan; Nazri Che Dom; Ahmad Razali Ishak; Samsuri Abdullah; Hasber Salim; Sharifah Norkhadijah Syed Ismail; Nopadol Precha (Environmental Science and Pollution Research, 2021)

Correction to: Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Stacked insecticidal genes in potatoes exhibit enhanced toxicity against Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) - Muhammad Salim; Allah Bakhsh; Ayhan Gökçe (Plant Biotechnology Reports, 2021)

Short term rainfall-runoff modelling using several machine learning methods and a conceptual event-based model - Rana Muhammad Adnan; Andrea Petroselli; Salim Heddam; Celso Augusto Guimarães Santos; Ozgur Kisi (Stochastic Environmental Research and Risk Assessment, 2021)

Comparison of different methodologies for rainfall–runoff modeling: machine learning vs conceptual approach - Rana Muhammad Adnan; Andrea Petroselli; Salim Heddam; Celso Augusto Guimarães Santos; Ozgur Kisi (Natural Hazards, 2021)

Revisiting the cytotoxicity of quantum dots: an in-depth overview - Sohrab Nikazar; Vishnu Sankar Sivasankarapillai; Abbas Rahdar; Salim Gasmi; P S Anumol; Muhammad Salman Shanavas (Biophysical Reviews, 2020)

Assessing Carbon Stock and Sequestration of the Tropical Seagrass Meadows in Indonesia - A’an J. Wahyudi; Susi Rahmawati; Andri Irawan; Hadiyanto Hadiyanto; Bayu Prayudha; Muhammad Hafizt; Afdal Afdal; Novi S. Adi; Agustin Rustam; Udhi. E. Hernawan; Yusmiana P. Rahayu; Marindah Y. Iswari; et al. (Ocean Science Journal, 2020)

Performance of Aeluropus lagopoides (mangrove grass) ecotypes, a potential turfgrass, under high saline conditions - Muhammad Zamin; Abdul Mateen Khattak; Abdul Mohsin Salim; Kenneth B. Marcum; Muhammad Shakur; Shahen Shah; Ibadullah Jan; Shah Fahad (Environmental Science and Pollution Research, 2019)

Association of detoxification enzymes with butene-fipronil in larvae and adults of Drosophila melanogaster - Muhammad Shahid Arain; Muhammad Shakeel; Mohammed Esmail Abdalla Elzaki; Muhammad Farooq; Muhammad Hafeez; Muhammad Rafiq Shahid; Syed Ali Haider Shah; Fawad Zafar Ahmad Khan; Qaiser Shakeel; Abdalla Markaz Abdalla Salim; Guo-Qing Li (Environmental Science and Pollution Research, 2018)

Quantitative interpretation of carbonate reservoir rock using wireline logs: a case study from Central Luconia, offshore Sarawak, Malaysia - Hammad Tariq Janjuhah; Ahmed Mohammad Ahmed Salim; Mumtaz Muhammad Shah; Deva Ghosh; Abubaker Alansari (Carbonates and Evaporites, 2017)

Modulation of antioxidant enzymes in Juniperus procera needles in relation to habitat environment and dieback incidence - Ibrahim M. Aref; Pervaiz R. Khan; Salim Khan; Hashim El-Atta; Abdalla I. Ahmed; Muhammad Iqbal (Trees, 2016)

The role of new eudesmane-type sesquiterpenoid and known eudesmane derivatives from the red alga Laurencia obtusa as potential antifungal–antitumour agents - Walied M. Alarif; Khalid O. Al-Footy; Muhammad Sulaiman Zubair; Mohamed Halid PH; Mohamed A. Ghandourah; Salim A. Basaif; Sultan S. Al-Lihaibi; Seif-Eldin N. Ayyad; Farid A. Badria (Natural Product Research, 2016)

Seroprevalence of Mycobacterium avium subspecies paratuberculosis (MAP) and evaluation of risk factors in camels of the Sultanate of Oman - Muhammad Hammad Hussain; Muhammad Saqib; Mahir Gharib Al-Maawali; Salim Al-Makhladi; Mohammed Somar Al-Zadjali; Talal Al-Sidairi; Saud Asubaihi; Abdulmajeed Al-Rawahi; Muhammad Khalid Mansoor (Tropical Animal Health and Production, 2015)

Geochemical study of the Cretaceous–Tertiary boundary succession exposed at Duhok Dam area (eastern Tethys): Northern Iraq - Muhammad S. Salih; Majid M. Al-Mutwali; Salim M. Aldabbagh (Arabian Journal of Geosciences, 2015)

Cheddar Cheese Ripening and Flavor Characterization: A Review - Mian Anjum Murtaza; Salim Ur-Rehman; Faqir Muhammad Anjum; Nuzhat Huma; Iram Hafiz (Critical Reviews in Food Science and Nutrition, 2014)

Granzyme M: characterization with sites of post-translational modification and specific sites of interaction with substrates and inhibitors - Rukhshan Khurshid; Mahjabeen Saleem; Muhammad Saleem Akhtar; Asmat Salim (Molecular Biology Reports, 2011)

Changes in water-extractability of soil inorganic phosphate induced by chloride and sulfate salts - Zahoor Ahmad; Faridullah; Haytham El-Sharkawi; Muhammad Irshad; Toshimasa Honna; Sadahiro Yamamoto; Ahmed Salim Al-Busaidi (Environmental Science and Pollution Research, 2008)

Indica rice varietal development in Pakistan: an overview - Khurram Bashir; Nasir Mahmood Khan; Sultana Rasheed; Muhammad Salim (Paddy and Water Environment, 2007)